PEMBUATAN SEDIAAN PARAM ANTIPANU RIMPANG LENGKUAS MERAH (Alpinia purpurata K.Schum) DARI BERAS (Oriza sativa L) SEBAGAI BAHAN PENGISI - Pratiwi, Tiwi; Putra, Risa Kota; Helmiawati, Yusi (Sekolah Tinggi Ilmu Kesehatan Holistik, 2018)
Background: The red galangal (Alpinia purpurata K.Schum) is one of the plants that has been known for its benefits by the people of Tanggulun Barat village RT.23/RW.06 Kalijati, Subang Regency, as swamedication to prevent and treat ringworm. However, medical thecnology developed for the majority of people tends to be synthetically made and does not have any herb characteristics at all, especially in the urban society. Objective: This research aims to produce Red Galangal Rhizomes (Alpinia purpurata K.Schum) anti-ringworm param supply from rice (Oriza sativa L) as stable filler organoleptically. Method: Etnofarmacology was used as a design in this research. This research begins with the accumulation of data through interview with the people of Tanggulun Barat village RT.23/RW. 06 Kalijati, Subang Regency which become the reference to produce param supply with variable time length of drying in the sunlight in the purpose to find out the effect of water content towards the stability of supply throughout storaging process. Param supply stability testing done by organoleptic observation in three storage variable. Result: Result shows that param supply which was dried in the sunlight for one day had a better color and aroma stability compared to two and three days of drying, while the organoleptic testing of supply results in the difference of form and fungus growth to be not found on all samples, however there have been changes on aroma and color on storage inside open and closed container with the silica gel. Conclusion: The conclusion of this research is that the param supply with the process of drying in the sunlight for one day with closed container storage without silica gel gives fine product and stability which can withstand up to three weeks.